Customer satisfaction survey on library collection. - Abdullah, Salmah (2011)
This paper aims to study the customer satisfaction level towards the library coliection. The library collection includes books, printed journals, online journals, online books and online databases. The research developed to determine the satisfaction of the user who used the library collection. It also examine whether any significant difference of satisfaction exist among library client towards the coliection. Data gathered through a self-administered survey given to random sampled 1,295 respondents inclusive of staffs and students of Universiti Putra Malaysia (UPM). The results obtained show that category of user and the library coliection status itself are the elements that have an impact on customer satisfaction. This paper concludes that different categories of user have different level of satisfaction towards library collection.